Aprender a ler para aprender geografia: desafios interdisciplinares - Paula, Suzana Ribeiro de (2018)
This Master's research aims to investigate the geography field, specifically the recurrent genres in this discipline in its compositional, linguistic and semantic-discursive aspects. Therefore, we start from the conception that the genders are configurations of meaning with a social purpose (ROSE; MARTIN, 2012). Martin points out that writing in science is different from writing in other parts of the curriculum. Thus, "being literate in science means understanding the technical language that is used"(MARTIN, 1993b, p. 186). In this sense, we can say that textbooks constitute scientific models of written language for students. Due to this, we understand that the reading and the writing in the basic education can be improved if the professor gives the pupils an explicit education of the act of reading and writing, whereas the particularities of each discipline. This research is placed in the qualitative and quantitative paradigm; therefore, it is necessary to quantify the linguistic resources that characterize the sorts to interpret them. This way, the emphasis is in the qualitative interpretation of the researcher that finds subsidies in the quantification of the linguistic elements. We select, as general analysis, the didactic book of Geography Araribá Project, 2010, of 6º and 9º year - published by Modern Editor, with Fernando Carlo Vedovate as responsible. The analysis contemplates two stages: i) contextual investigation of the didactic book of Geography, with focus in the PNLD; and ii) literal-discursive investigation, focusing the variable of the context, the lexicon-grammatical characteristics and semantic-discursive (HALLIDAY and MATTHIESSEN, 2014) and the taxonomy proposed by the Functional Systemic Linguistics and thematic structure (MARTIN, ROSE, 2008), (MOYANO, 2013b). From the analysis of the data, it was concluded that the family of recurrent sorts is of the Reports and the Explanations.The Descriptive,Classified and Compositional Reports classify a phenomenon and describe its characteristics, whose intention is “to say what it is” and “as it is”. Explanations of the factorial and consequential type contribute to evidence the causes and consequences of the phenomena. The purpose of the Explanations is to say "how" and "why" phenomena happen. The Stages and Phases that make up the genres fulfill their purpose and contribute to reach the goal of the analyzed units.